Hyperuricemia prevalence and its risk factors in uremic patients undergoing maintenance hemodialysis - Meng Zhang; Gaoqiankun Huang; Xiaorong Bao; Qingmei Yang (BMC Nephrology)
Abstract Background To explore the prevalence of hyperuricemia and its associated factors in uremic patients undergoing maintenance hemodialysis (MHD). Methods Two hundred two uremic patients undergoing MHD for ≥ 3 months, in Jinshan Hospital, Fudan University, were enrolled. Pre-dialysis blood samples were tested during March 1st, 2023 to April 30th, 2023. Demographic characteristics were recorded. The prevalence of hyperuricemia, defined as serum uric acid (SUA) ≥ 420 μmol/L, was investigated. Individuals were divided into hyperuricemia (HUA) and non-hyperuricemia (n-HUA) groups. The demographic characteristics, residual kidney function, nutritional status, acid–base metabolism, electrolyte and lipid metabolism were compared between groups. The associated factors for hyperuricemia in MHD patients were identified by logistic regression. Results The median SUA level of the enrolled patients was 458.50 (392.25, 510.75) μmol/L. 134 (66.34%) candidates met the diagnostic criteria of hyperuricemia. The median SUA level in HUA group was 491.00 (459.50, 543.50) μmol/L. Compared to those in n-HUA group, subjects in HUA group showed lower estimated glomerular filtration rate and blood CO2 level, but higher levels of body mass index, geriatric nutritional risk index, plasma phosphate, potassium, pre-albumin, albumin, serum creatinine (Scr) and urea nitrogen. Logistic regression indicated that Scr (OR 1.002, 95% CI 1.001–1.004, P = 0.003), albumin (OR 1.165, 95%CI 1.011–1.342, P = 0.035), and blood potassium (OR 1.673, 95% CI 1.009–2.773, P = 0.046) were associated factors for hyperuricemia in uremic patients undergoing MHD. Conclusion Hyperuricemia was highly prevalent among uremic MHD patients. Elevated levels of Scr, albumin and plasma potassium were independent associated factors for hyperuricemia.